Potensi Buah Rimbang (Solanum torvum Sw.) sebagai Analgetik dengan Metode Induksi Asam Asetat dan plantar test - Utami, Dinda Sari; Nasution, Melvi Ariati; Fauzi, Ziza Putri Aisyia; Sari, Syilvi Rinda; Hartini, Putri Tri; Rawitri, Kiki (Journal of Pharmaceutical and Health Research, 2024)
Abstract is Solanum torvum is a traditional medicine plant ingredient for treating stomach disease, relieving pain (analgesic), initiating blood circulation, removing cough (anti-tussing) and anti-inflammatory. At this examination, a phytochemical screening of powder and fruit extracts has been carried out. Simplicity characteristic tests and analgesic effect tests with acetate acid induction method and plantar tests with suspensions of ethanol extract are given in doses of 500, 1000 and 2000 mg/kgBB, metampiron suspense 2% positive ontrol, CMC suspense 0.5% as negative control as well as gland data are analyzed with ANOVA method. Results of screening of phytomia powder and ethanole extract contains secondary metabolite compounds of the classes of alkaloids, tannins, saponins, flavonoids, steoids and glycosides. Characteristic results of simplisia powder are 8% water content, 5.3% total ash content, 29.6% water-soluble sulphur content, 18.9% ethanol-solubility, 0.48% acid-insoluble ash content. Ethanol extract with 2000 mg/kgBB acetate acid induction method has the highest analgesic strength and effectiveness percentage of 55.9% and 86.04% for plantar test methods with hight analgetic values with 29,3±1,7 second.